Construction of lncRNA-related competing endogenous RNA network and identification of hub genes in recurrent implantation failure - Jialyu Huang; Ning Song; Leizhen Xia; Lifeng Tian; Jun Tan; Qianqian Chen; Jing Zhu; Qiongfang Wu (BMC, 2021)
Abstract Background The mechanism of recurrent implantation failure (RIF) is unclear at present and poor endometrial receptivity may be one of the leading reasons. This study aims to construct a competing endogenous RNA (ceRNA) network and identify potential hub genes underlying the development of RIF. Methods Weighted gene co-expression network analysis was performed based on differentially expressed mRNAs (DEMs) and lncRNAs (DELs) from the GSE111974 dataset. Functional enrichment analyses of gene modules were conducted using Gene Ontology classification and Kyoto Encyclopedia of Genes and Genomes pathway. A lncRNA-miRNA-mRNA ceRNA regulatory network was constructed according to predictive interaction derived from the LncRNADisease, miRTarBase, miRDB and TargetScan databases. Topological analysis determined the key genes with the highest centroid and their expressions were further verified using public datasets and quantitative real-time polymerase chain reaction. Results A total of 1500 DEMs and 3 DELs were significantly up-regulated, whereas 1022 DEMs and 4 DELs were significantly down-regulated in the RIF group compared with the control group. Six functional co-expression modules were enriched in various biological processes, such as cell adhesion, regulation of cell motility and cellular response to vascular endothelial growth factor stimulus. Five hub genes were identified in the ceRNA network, of which GJA1 was down-regulated whereas TET2, MAP2K6, LRRC1 and TRPM6 were up-regulated in RIF endometrium. Conclusions We constructed a lncRNA-associated ceRNA network and identified five novel hub genes in RIF. This finding could be helpful to understand the molecular mechanism for RIF pathogenesis, and may provide novel insights for its early diagnosis and treatment.